(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
Urea is hydrolyzed by means of urease enzyme with production of ammonia and carbonic acid. It provides an alkaline pH, and leads to CaCO3precipitation.This are one of the mechanisms for microbially induced calcium carbonate precipitation (MICP). For this study, ureolytic bacteria capable of precipitating calcium carbonate were isolated from different types of soil samples and were tested for their urease activity. Each isolate was identified morphologically and using basic biochemical tests. Isolates were also further tested for their ability to grow in extreme environment such as high pH, high salt concentration and low nutrient availability. 16 out of 28 isolates showed positive results for urease production. Hydrolysis of urea was examined using Christensen’s urea agar base. Conductivity method was used to assay urease activity and it was in the range of 0.009-0.051 mS/min. Calcium carbonate precipitation via urea hydrolysis was investigated in both solid and broth media. CaCO3crystals in the precipitation agar media were imaged. The present experimental approach can be potentially useful for a variety of environmental bioremediation applications such as heavy metal removal, self-healing concrete etc.